ANALISIS STRATEGI DIFERENSIASI PRODUK TERHADAP KEPUASAN KONSUMEN - Hartiwi Agustina (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2017)
This research aims to know the differential strategy consisting of product function-based differential strategy, form of product-based differential strategy and subjective attribute-baseddifferential strategy that can give effects on the customer satisfaction by using a product.Population in this research was all customers of Samsung mobile phone. Sample determination was by accidental sampling while determination on number of sample used a formula by Suprantoand it was obtained number of sample by 100 people. Variables in this research consist of product function-based differential strategy, form of product-based differential strategy and subjective attribute-based differential strategy as independent variables and customer satisfaction as the dependent variable.Data collection method used questionnaire. Data analysis used multiple regression analysis.Results of the research show that the Nokia product function-based differential strategy has been good (75,90%), the form of product-based differential strategy has been good (73,47%), attribute subjective-based differential strategy has been good (75,90%) and the customer satisfaction has be in satisfied category (74,65%).Results of the analysis were obtained the regression equation by:Yˆ=8,804+0,370X1 +0,424X2+0,172X3. Meaningful test of regression coefficient with t test was obtained tcountfor variable of product function-based differential strategy by 4,422 with significance by 0,000,tcountfor variable of form of product-based differential strategy by 4,926with significance by 0,000,and tcount for variable of subjective attribute-based differential strategy by 2,122with significance by 0,036.Because the significance values of the three variable were less than 0,05so that it can be concluded that the product function-based differential strategy, form of product-based differential strategy and subjective attribute-based differential strategy influence partially on the customer satisfaction. This, it can be concluded that simultaneously, the product function-based differential strategy, form of product-based differential strategy and subjective attribute-based differential strategy partially influence on the customer satisfaction namely by 66,5%.Keywords: product differentiation, customer satisfaction